Spending More, Fewer Casualties? Leveraging Governance in Local Disaster Management - Suksesi, Gita; Qibthiyyah, Riatu Mariatul (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2025)
Research Originality: This research introduces a quantitative framework for evaluating the effectiveness of local government disaster management strategies in Indonesia, specifically during the pre-disaster and emergency response stages—an area previously underexplored in existing qualitative-focused literature. Research Objectives: This study evaluates the effectiveness of disaster management in reducing losses from natural disasters, focusing on two main stages: the pre-disaster and emergency response stages. Pre-disaster is measured by the documented availability of the Disaster Management Plan and the emergency response aspect through emergency spending. Research Methods: This study employs fixed-effect estimation using panel data from districts and cities across Indonesia spanning 15 years, from 2008 to 2022. Empirical Results: The study's results indicate that RPB effectively reduces the death rate from natural disasters, whereas the realization of BTT shows the opposite result. Implications: These findings indicate that local governments should improve the quality of their RPBs and regularly prepare them to mitigate disaster risk effectively. Additionally, the government needs to assess and improve the flexibility of the BTT implementation mechanism, enabling its immediate use during the initial emergency response stage and thereby reducing death rates from natural disasters. JEL Classification: Q54, Q58, H72 How to Cite:Suksesi, G., & Qibthiyyah, R. M. (2024). Spending More, Fewer Casualties? Leveraging Governance in Local Disaster Management. Signifikan: Jurnal Ilmu Ekonomi, 14(2), 391-406. https://doi.org/10.15408/sjie.v14i2.46416.